2016
DOI: 10.1016/j.biomaterials.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Thailandepsin A-loaded and octreotide-functionalized unimolecular micelles for targeted neuroendocrine cancer therapy

Abstract: Due to the overexpression of somatostatin receptors in neuroendocrine (NE) cancers, drug nanocarriers conjugated with somatostatin analogs, such as octreotide (OCT), for targeted NE cancer therapy may offer increased therapeutic efficacies and decreased adverse effects. In this study, OCT-functionalized unimolecular micelles were prepared using individual hyperbranched polymer molecules consisting of a hyperbranched polymer core (Boltorn® H40) and approximately 25 amphiphilic polylactide-poly(-ethlyene glycol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 49 publications
(43 reference statements)
1
45
0
2
Order By: Relevance
“…1 (C)) [18, 19]. In addition, we previously reported that TDP-A-loaded octreotide-conjugated unimolecular micelles induced 74% of tumor reduction compared to the control, also measured 20 days after the first injection using the same TDP-A dosage, same treatment schedule, and same tumor model [48]. This may be another indication that KE108 was more effective than octreotide as an NE tumor-targeting ligand for drug nanocarriers.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…1 (C)) [18, 19]. In addition, we previously reported that TDP-A-loaded octreotide-conjugated unimolecular micelles induced 74% of tumor reduction compared to the control, also measured 20 days after the first injection using the same TDP-A dosage, same treatment schedule, and same tumor model [48]. This may be another indication that KE108 was more effective than octreotide as an NE tumor-targeting ligand for drug nanocarriers.…”
Section: Resultsmentioning
confidence: 78%
“…Figure 5 shows the SSTR 1–5 expression levels in BON and MZ–CRC–1 cells. Our previous studies demonstrated that octreotide—which has a high affinity for SSTR2 and a moderate affinity for SSTR5—increased the cellular uptake of the micelles about 4-fold compared with non-targeted micelles in BON cells [48]. The KE108 peptide—which displays high affinity for all 5 subtypes of SSTRs (SSTR 1–5)—should exhibit much higher cellular uptake than octreotide.…”
Section: Resultsmentioning
confidence: 99%
“…small molecules, peptides, antibodies, and aptamers) and imaging probes (e.g., dyes, radioisotopes, etc.) 2730 .…”
Section: Introductionmentioning
confidence: 99%
“…Other models oriented on micellar organization deal with dynamic forms [11], including micellar aggregates studied in the context of membrane proteins [12,13]. Studies of micellar forms and their applications in drug transport can be found in [14][15][16][17][18][19]. Notably, the ability to construct a co-micelle (i.e., …”
Section: Introductionmentioning
confidence: 99%